2018
DOI: 10.1186/s13075-018-1653-5
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of synovitis and arrest of catabolic and anabolic bone changes in patients with psoriatic arthritis by IL-17A blockade with secukinumab: results from the prospective PSARTROS study

Abstract: BackgroundAlthough the effects of interleukin-17A (IL-17A) inhibition on the signs and symptoms of psoriatic arthritis (PsA) are well defined, little is known about its impact of local inflammatory and structural changes in the joints. The PSARTROS study was designed to elucidate the effects of IL-17A inhibition on inflammation and bone changes in joints affected by PsA.MethodsThis was a prospective open-label study in 20 patients with active PsA receiving 24 weeks of treatment with the IL-17A inhibitor secuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 32 publications
2
51
0
3
Order By: Relevance
“…These data show that inhibition of IL-17A by secukinumab leads to profound changes in general, physical, and mental health perception of PsA patients in addition to the objective improvement in signs and symptoms and imaging findings of inflammation, which have been reported previously [5,6]. While the effects of secukinumab on pain and physical function observed in established PsA are not surprising and have already been observed in the large phase 3 studies [7][8][9], in which ACR responses comprising pain and function are used as outcomes, the substantial effects of secukinumab treatment on other PROs that are not directly related to pain and physical function, such as social functioning, vitality, mental health, and emotional role limitation are interesting and suggest a much deeper modification of the health state of PsA patients than previously considered.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These data show that inhibition of IL-17A by secukinumab leads to profound changes in general, physical, and mental health perception of PsA patients in addition to the objective improvement in signs and symptoms and imaging findings of inflammation, which have been reported previously [5,6]. While the effects of secukinumab on pain and physical function observed in established PsA are not surprising and have already been observed in the large phase 3 studies [7][8][9], in which ACR responses comprising pain and function are used as outcomes, the substantial effects of secukinumab treatment on other PROs that are not directly related to pain and physical function, such as social functioning, vitality, mental health, and emotional role limitation are interesting and suggest a much deeper modification of the health state of PsA patients than previously considered.…”
Section: Discussionsupporting
confidence: 82%
“…Patients from the IVEPsA study [6] on very early PsA (N = 20) and the PSARTROS [5] study on established PsA (N = 20) were included in this analysis. The very early PsA patients of the IVEPsA study were required to fulfill the following criteria: (i) presence of moderate to severe psoriasis (PASI score > 6) or scalp or nail involvement; (ii) absence of present or past joint swelling, active enthesitis, or dactylitis; and (iii) presence of subclinical inflammatory changes in magnetic resonance imaging (MRI) or erosive changes in MRI or high-resolution peripheral quantitative computed tomography (HR-pQCT).…”
Section: Study Populationmentioning
confidence: 99%
“…Clinical data in patients with PsA show a significant reduction in joint radiographic progression with IL-17A inhibitors versus placebo in the short-term and low long-term rates of radiographic progression 13 14 129. Furthermore, recent data from the PSARTROS study showed no progression of catabolic and anabolic bone changes in the joints of patients with PsA treated with secukinumab for 24 weeks 130…”
Section: Role Of Il-17a In Spamentioning
confidence: 99%
“…These results suggest that psoriasis patients who will develop PsA soon after diagnosis of psoriasis could be identified by unspecific arthritic symptoms and should therefore receive rheumatological care. Recent evidence suggests that early intervention treatment of PsA with biologic disease-modifying anti-rheumatic drugs (DMARDs) halts the progression of bone changes and decreases synovial inflammation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%